1996
DOI: 10.1097/00005768-199603000-00012
|View full text |Cite
|
Sign up to set email alerts
|

Cardiorespiratory capacity of individuals with mental retardation including Down syndrome

Abstract: This study evaluated the cardiorespiratory capacity of persons with MR with and without Down syndrome. Analyses of individual data records of maximal exercise tests with metabolic analyses were conducted on tests of 111 subjects (31 men and 16 women with DS; 35 men and 29 women without DS) from six participating centers. All centers used a walking treadmill protocol previously shown to produce valid and reliable maximal tests with this population. Peak oxygen uptake and peak minute ventilation were higher in m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
92
2
3

Year Published

2006
2006
2012
2012

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 105 publications
(101 citation statements)
references
References 17 publications
4
92
2
3
Order By: Relevance
“…Since there is sufficient evidence that some impairments associated with Down syndrome (e.g., joint hypermobility, obesity, low bone mass) negatively impact health factors such as physical fitness [Fernhall et al, 1996], specific diagnosis must be considered when studying physical activity in people with MR.…”
Section: Demographic and Biological Factors And Behavioral Attributesmentioning
confidence: 99%
“…Since there is sufficient evidence that some impairments associated with Down syndrome (e.g., joint hypermobility, obesity, low bone mass) negatively impact health factors such as physical fitness [Fernhall et al, 1996], specific diagnosis must be considered when studying physical activity in people with MR.…”
Section: Demographic and Biological Factors And Behavioral Attributesmentioning
confidence: 99%
“…When controlling for thyroid dysfunction, resting metabolic rate in obese DS individuals is not reduced, implying that when children with DS have low resting metabolic rates, it may predispose them to obesity as adults . The high incidence of obesity in DS individuals is mainly attributed to sedentary lifestyle (Dodd et al, 2005;Rimmer et al, 2004;Tsimaras et al, 2003;Carmeli et al, 2002 b ;Fernhall et al, 1996;Fernhall et al, 1993;Pitetti et al, 1993 andPitetti et al, 1991). The problem is exacerbated by the fact that adults with DS face considerable barriers to participation in health promotion programs .…”
Section: B Causes and Characteristics Of Dsmentioning
confidence: 99%
“…The physiological characteristics of the Down's syndrome individual provide potential limitations and restrictions to both cardiovascular and resistance based exercise tolerance (Shields et al, 2008;Rimmer et al, 2004;Tsimaras et al, 2003;Varela et al, 2001;Millar et al, 1993), with heart abnormalities, poor skeletal muscle development and chronotropic incompetence (CI) being the primary constraints (Fernhall et al, 1996). Additionaly, Barnhart et al (2007) found that lower lean muscle mass and higher incidences of obesity could also be contributory to the lower cardiovascular capacity of DS individuals.…”
Section: Maximal and Submaximal Exercise Capacitymentioning
confidence: 99%
See 2 more Smart Citations